The Christian family in changing times : the myths, models, and mystery of family life - Hicks, Robert, 1945- (Grand Rapids, MI. Baker Books., 2002)
With courage and gentleness, Robert Hicks dares to lift the curtain of correctness surrounding the American church's emphasis on the family and inspects its biblical underpinnings. Why is it, he asks, that after thirty years of reading and hearing and talking about the Christian family, instead of growing stronger and healthier, instead of having a deeper impact on the culture around us, the family is worse off than ever? His answer is that the popular mental image of the Christian family is not a truly biblical expression but rather a cultural and romantic notion rooted in one particular time and place. After examining the possible origins of the current American concept of the Christian home, he exposes its common myths, presents an overview of the biblical examples and teachings on family, and then offers a rethinking of theology for a healthy, Christ-centered family. This refreshing look at the scriptural model for family relationships and responsibilities is at first unsettling but ultimately liberating, placing Jesus Christ and the will of his Father at the center of the family of God. - Publisher.
So what changed about family life? -- How Hollywood taught me to think about family -- Common myths about the Christian family -- What biblical families look like in the Old Testament -- What the Bible says about families in the New Testament.
Includes bibliographical references (pages 150-159).
Keywords: Families -- Religious aspects -- Christianity; Families -- Biblical teaching